The Contemporary Financial Architecture in Latin America - Natalia Khmelevskaya (Ибероамериканские тетради, 2016)
The regional ﬁnancial architecture of Latin America is in the focus of this article, from the author’s point of view. There are intergovernmental and hybrid multilateral ﬁnancial institutions which provide ﬁnance within oﬃcial development assistance. IADB, CDB and CABEI present the ﬁrst type of ﬁnancing, while BLADEX and CAF are coﬁnancing type in discussion. Hence, their practices and credit portfolios are analyzed to emphasis speciﬁc. The Latin America Reserve Fund (FLAR) has been created to cushion liquidity in case of sudden stops in capital ﬂows and trade deﬁcit.